Effect of the storage in water on the radiopacity of calcium hydroxide cements - Karina Lopes Devito; Ana Isabel Ortega Ortega; Francisco Haiter-Neto (Universidade Estadual de Campinas, 2015)
In extensive cavities usually calcium hydroxide cements are used in order to protect the pulp. These materials can present a reduction in the radiopacity due solubility resulting from contact with oral fluids. This study investigated the radiopacity of calcium hydroxide cements stored in distilled water at 37o C, with the aim to verify the alteration of radiographic density in function of solubility. Samples of Dycal, Hydro-C and Life cements were submitted to immersion for periods of 3, 7, 30 and 60 days. After each of these periods, the samples were radiographed and their optical densities obtained. The radiopacity values were expressed in equivalent thickness of aluminum and were compared with the values of enamel and dentine. ANOVA was used to determine if there was a significant difference between the radiopacity values of the cements submitted to different immersion times. The results showed that Dycal and Hydro-C cements presented a significant radiopacity reduction after one week of immersion, while Life had its radiopacity significantly reduced only after 2 months. However, the three tested cements kept similar radiopacity values to those of enamel.